Interhemispheric differences in polar stratospheric HNO3, H2O, ClO, and O3 - Jarnot, R. F.; Peckham, G. E.; Manney, G. L.; Waters, J. W.; Flower, D. A.; Froidevaux, L.; Harwood, R. S.; Read, W. G.; Santee, M. L. (1995)
Simultaneous global measurements of nitric acid (HNO3), water (H2O), chlorine monoxide (ClO), and ozone (O3) in the stratosphere have been obtained over complete annual cycles in both hemispheres by the Microwave Limb Sounder on the Upper Atmosphere Research Satellite. A sizeable decrease in gas-phase HNO3 was evident in the lower stratospheric vortex over Antarctica by early June 1992, followed by a significant reduction in gas-phase H2O after mid-July. By mid-August, near the time of peak ClO, abundances of gas-phase HNO3 and H2O were extremely low. The concentrations of HNO3 and H2O over Antarctica remained depressed into November, well after temperatures in the lower stratosphere had risen above the evaporation threshold for polar stratospheric clouds, implying that denitrification and dehydration had occurred. No large decreases in either gas-phase HNO3 or H2O were observed in the 1992-1993 Arctic winter vortex. Although ClO was enhanced over the Arctic as it was over the Antarctic, Arctic O3 depletion was substantially smaller than that over Antarctica. A major factor currently limiting the formation of an Arctic ozone 'hole' is the lack of denitrification in the northern polar vortex, but future cooling of the lower stratosphere could lead to more intense denitrification and consequently larger losses of Arctic ozone.